Model empati siswa: Peran kompetensi sosio emosional sebagai mediator pada konsep diri dan iklim sekolah: Student empathy model: The role of socio-emotional competence as a mediator in self-concept and school climate - Yuniwati, Esy Suraeni; Bambang Budi Wiyono; Imanuel Hitipeuw; Ika Andrini Farida (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Empathy is an important asset in building conducive social relationships and forming a caring and responsible personality in the future. The formation of empathy can be influenced by internal and external factors. This study aims to examine the influence of school climate, self-concept and socio-emotional competence on the formation of empathy in adolescents. The research design used a quantitative approach with participants of adolescent high school students (n = 377) selected by cluster random sampling. Empathy was measured using the Interpersonal Reactivity Indeks-IRI Scale(α=0,978), school climate was measured with The School Climate Measure Scale-SCM (α=0,936), self-concept was measured with the Personal Self Concept PSC Scale-PSC (α=0,798), and socio-emotional competence was measured using The Delaware Social-Emotional Competence Scale DSEC (α=0,880). The analysis technique used is the Structural Equation Model (SEM) which is processed using AMOS software. The results showed that the proposed research model can be supported by empirical data. This means that a positive school climate and a healthy self-concept together create an environment that supports the development of empathy in adolescents.